Description of The Tatwa Kusumadewa Contents as Guidelines of Pinandita in Hindu Religious Ceremonies - Widana, I Nyoman Murba (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2024)
This research aims to describe the contents of the kusumadewa tattwa which is used as a guideline in the implementation of Hindu religious ceremonies in Mataram City, West Nusa Tenggara and Kupang City, East Nusa Tenggara. This research was designed as a qualitative descriptive type in order to describe the contents of the kusumadewa tattwa. This research obtained the results that Lontar tattwa kusumadewa contains teachings related to ethics that must be carried out by Hindu holy people, especially pinandita or pemangku in carrying out Hindu religious ceremonies. There are several ethics called sesana that must be adhered to by the pinandita or pemangku in the tattwa kusumadewa, such as (1) the sesana of pinandita or pemangku in carrying out swadharma which includes vishaya karma and sreya karma, (2) the tata kramaning of being a pemangku widhi through mawinten Agung and mediksha widhi , (3) multi-purpose guidelines which emphasize the wisdom that must be carried out by the pinandita or pemangku, (4) life and courage which involves the attitude of cultivating courage in carrying out the dharma, (5) Acting to purify the heart, namely the pemangku should do tapa, brata, semadi in carrying out God's orders on Hindu religious holy days, such as purnama, tilem, and other holy days.